Microstructure evolution and corrosion behavior of Ti-29Nb-13Ta-4.6Zr nano-biocomposite fabricated by friction stir processing in simulated body fluid solution. (6th September 2019) - Rajabi, F; Zarei Hanzaki, A; Abedi, H R; Hoseiny, H; Najdahmadi, A; Bertrand, E
Abstract: The present work deals with the microstructure evolution and corrosion behavior of thermomechanically processed Ti-29Nb-13Ta-4.6Zr (TNTZ) nano biocomposite. The nano Fluorine Apatite (nFA) particles holding acicular morphology with the size of <100 nm, were added to the work-pieces through friction stir processing. The corrosion behavior was investigated in simulated body fluid (SBF) at 37° representing the human body temperature. For further clarification, the obtained results were compared with those obtained for homogenized condition and the processed materials without powder. The results indicated the high capability of the material for microstructure refinement in the course of friction stir processing, e.g. the mean grain size of 5 μ m only after three number of the passes. It was found that the corrosion resistance was significantly improved compared to the homogenized material. Decrease in the grain size, the homogeneous dispersion of nano particles, and the substructure development were found as the main factor influencing on the corrosion resistance. The best electrochemical response was achieved after three passes processing of the biomaterial containing nano powders.